Imagining future events in patients with unilateral temporal lobe epilepsy. (18th February 2016) - Lechowicz, Meryn; Miller, Laurie; Irish, Muireann; Addis, Donna Rose; Mohamed, Armin; Lah, Suncica
Abstract : Objectives: Imagining future events, which contain episodic and non‐episodic details, has been found to (1) engage the temporal lobes bilaterally and (2) be impaired in patients with bilateral temporal lobe pathology. Here, we examined whether unilateral temporal lobe dysfunction also impairs the ability to generate future events. Design: Prospective cross‐sectional. Methods: Twenty patients with a history of unilateral temporal lobe epilepsy [TLE; 10 left (LTLE) and 10 right (RTLE)] and 20 normal control (NC) subjects comparable on age, sex and education completed the Adapted Autobiographical Interview, which required recall of past and generation of future events and distinguished episodic (internal) from non‐episodic (external) details. Participants also completed a battery of neuropsychological tests. Results: Patients with unilateral TLE were significantly impaired in provision of internal details for past and future events, but not in the generation of external details. Examination of detail subcategories revealed that patients with LTLE did exhibit a significant deficit relative to patients with RTLE (and NC) with respect to the generation of perceptual details for both past and future events. Moreover, patients with LTLE generated significantly fewer place details for future events (relative to NC only). The overall number of internal details recalled by patients with LTLE was related to semantic fluency. Conclusions: Our study provides the first evidence that unilateral temporal lobe dysfunction is associated with not only impaired recall of past, but also the generation of future episodic details. Clinically, deficits in future thinking may reduce motivation and decision‐making, and as such adversely impact behavioural regulation and socialization. Practitioner points: Patients with temporal lobe epilepsy generate less details when asked to describe past and potential future events, particularly with regard to details involving specific events, places and perceptions. These same patients are aware of their difficulties in this realm, but judge their past memories as similar in vividness and even more personally significant than the memories generated by control participants. The deficits in generation of future episodic details were particularly pronounced in patients with left temporal lobe epilepsy. Verbal semantic fluency was correlated with the ability to generate future scenarios.